(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Although considerable research attention has been given to the domain of online service failure and recovery in the recent years, extant literature has been inconclusive on the relative impact of each dimension of justice on post recovery customer outcomes following a successful service recovery. Hence this study examines the impact of online service recovery on post recovery customer outcomes as a result of varying justice dimensions such as distributional, procedural and interactional. A scenario-based role-playing survey was done among 325 Indian online hospitality customers in and results from a structural equation modelling revealed that distributive justice had the highest impact among the three dimensions of justice. The study provides significant contribution to both theory and practice which helps the managers to design robust strategies for addressing service failures in a hospitality context.